Perceived Social Support And Psychological Well-Being Among Interstate Students At Malikussaleh University - Adyani, Liza; Suzanna, Ella; Safuwan, Safuwan; Muryali, Muryali (Universitas Muhammadiyah Surakarta, 2018)
This study aims to examine the relationship between perceived social support and psychological well-being among interstate students at Malikussaleh University, Lhokseumawe. It is hypothesized that there will be positive relationship between perceived social support and psychological well-being. As the second largest state university in Aceh, students at Malikussaleh University come from different parts of Aceh and Indonesia. Thus, it is important to understand their psychological well-being as it will help them to be more satisfied and happy while being a way home. A number of 105 interstate students were participated in this study by answering a set of questionnaire. The questionnaire was provided online by using google docs platform. To obtain deeper meaning of their experiences, 10 students were selected to join focus group discussion (FGD). The collected data were analyzed by using correlation Pearson product moment. The result showed that there wasa positive correlation between perceived social support and psychological well-being with r = 0.40 and p = 0.000 (p 0.05). Additional findings from FGD are also included in discussion section.